Critical analysis on Implementation of GIS on Indenting of Sarva Siksha Abhiyan Schools. - Kumar Devadutta, Santosh Kumar Pani, Abhishek Kumar (Mathematical Statistician and Engineering Applications, 2022)
In the 21st century, the world has witnessed mammoth & monumental technological development, scientific advancement, economic progress & tremendous growth in every walk of life. Heuristic observation & Empirical estimation discovered that a major chunk of children in the developing countries are yet to be empowered with education. At this backdrop, India has initiated a wide range of educational programme with a broader spectrum to promote & popularize elementary education. One such profound & prudent educational programme is the Sarva Siksha Abhiyan [SSA].Its objective is to provide free education to all the children in the age-group of 6 years to 14 years. To deal with such a gigantic initiative which is exceedingly supported by extensive resource engagement, expansive infrastructural build-out, massive fund-flow, robust operational framework , collaborative & cohesive effort of central government, state government & local governance system, Several studies has identified a common area of concern, that is, having prodigious operational framework, the enrollment & retention of students in the school is not very encouraging & encompassing. To manage , monitor & maintain the programme that has a massive geographic spread & diversified demographic mix, is a colossal challenge. A comprehensive study has been made upon a district called Ganjam of the state Odisha to establish a simple ,smooth, seamless & sustainable operational system. It has been envisaged to come up with a real-time location-based indenting system to elevate & uplift the programme to attend & achieve the programme objectives.